Glycerol dry reforming for syngas production over ag-promoted on ni-based catalysts - Norazimah, Harun (2017)
The use of glycerol has been widely investigated and one of the possible alternatives is as a feedstock in the production of synthesis gas (syngas). The glycerol CO2 dry reforming process is an attractive process as it converts carbon dioxide, a greenhouse gas, into a synthesis gas and simultaneously removed from the carbon biosphere cycle. The main objective of this research work is to study the process of CO2 dry reforming of glycerol over noble catalyst i.e. a noble metal (silver) promoted on nickel-based catalyst supported on oxides (aluminium oxide and silicon oxide). Silver is rarely used as catalyst in reforming studies. However, it is proven that silver has the ability to reduce the carbon deposition and increase selectivity of hydrogen production besides lower in cost compared to other noble metal. The catalysts were formulated through wet impregnation method using different combinations of noble metal-oxides support. Their physicochemical characteristics were evaluated using nitrogen physisorption (Brunauer-Emmet-Teller (BET) method), X-ray diffraction (XRD), Scanning electron microscopy (SEM), Temperature programmed calcination (TPC), Temperature programmed reduction (H2-TPR) and Temperature programmed desorption (TPD). The screening study was conducted to evaluate the performance of different types of supports, and it was found that Ni/Al2O3 catalyst series gave higher glycerol conversion and hydrogen yield compared to Ni/SiO2 catalyst series due to their small crystallites size and high surface area. Moreover, alumina support could increase metal dispersion as well as avoiding the carbon deposition, which simultaneously improved the activity and stability of the catalyst. Apart from that, when different Ag loadings were introduced to these catalysts, 3wt% of Ag in Ni/Al2O3 was found to give the best catalyst performance due to the well-dispersion of active sites on the catalyst surface, which created high surface area. Higher Ag loading (>3wt%) resulted in formation of small particles, which covered the active sites of the catalyst thus impaired the catalyst performance. Further investigation on the effect of reaction variables (i.e. reaction temperature, weight hourly space velocity (WHSV) and CO2-to-glycerol ratio (CGR)) to the production of syngas were conducted using the best catalyst obtained from the screening study. The best reaction condition was found at temperature of 1073 K, CGR of 1 and WHSV of 36 L gcat-1 h-1 (catalyst loading of 0.2 g) which gave 41.09% glycerol conversion and 32.31% hydrogen yield. During the catalyst longevity study, Ag(3)-Ni/Al2O3 was found to stabilise along the 72 hours reaction after experiencing a reduction at tenth hour. Apart from that, the study on the catalyst deactivation of the used catalyst shows the presence of filamentous and encapsulated carbon types on the catalyst surface, which can be removed through oxidation.